2010
DOI: 10.1103/physrevb.81.024109
|View full text |Cite
|
Sign up to set email alerts
|

Trapping of oxygen vacancies in the twin walls of perovskite

Abstract: The binding and pairwise interaction of oxygen vacancies in the ferroelastic ͑100͒ twin walls of the orthorhombic phase of CaTiO 3 perovskite ͑Pbnm͒ have been investigated by numerical simulations using empirical force fields. An oxygen vacancy finds it energetically favorable to reside inside a twin wall, particularly when bridging two titanium ions located in the twin-wall plane. In such case, the binding energy of the vacancy to the wall is 0.7Ϯ 0.1 eV, the error bar reflecting variability within two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
51
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 40 publications
2
51
0
Order By: Relevance
“…The first and main report of polar interfaces in non-polar materials was in CaTiO 3 : A large spontaneous polarization was predicted in {100} twin walls of CaTiO 3 , a definitely non-polar material. 20 Subsequent experimental studies using transmission electron microscopy 22 and second harmonic generation (SHG) confirmed such wall polarity. 23,24 Similar behavior was attributed to multidomain boundaries with distinct polar and oxygen octahedral tilting in BiFeO 3 ab initio simulations.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…The first and main report of polar interfaces in non-polar materials was in CaTiO 3 : A large spontaneous polarization was predicted in {100} twin walls of CaTiO 3 , a definitely non-polar material. 20 Subsequent experimental studies using transmission electron microscopy 22 and second harmonic generation (SHG) confirmed such wall polarity. 23,24 Similar behavior was attributed to multidomain boundaries with distinct polar and oxygen octahedral tilting in BiFeO 3 ab initio simulations.…”
mentioning
confidence: 97%
“…36 The discrepancy, caused by polarization terms, between experimental determination and available classical pair potentials is well known and described elsewhere. 44 Employing standard definitions of octahedral tilting, 7,8,20,45 we found a tilt angle of 9 -11 , formed around each Ti atom in the annealed bulk tetragonal system.…”
mentioning
confidence: 99%
“…In addition to the strain-induced ferroelectric behavior of thin films, the twin walls of CaTiO 3 have been extensively investigated, including trapping of oxygen vacancies 23,24 , the activation energy for twin-wall motion…”
mentioning
confidence: 99%
“…We also tried to fit the temperature dependence of τ DW with an Arrhenius law, yielding an energy barrier of E a ~ 0.58 eV. This is slightly lower than the value usually found in perovskites for pinning of DW's to oxygen defects 30,31 . However, as clearly seen in Fig.…”
Section: Discussionmentioning
confidence: 98%